Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/cjce.20649
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mass transfer coefficients in a pulsed disc and doughnut extraction column

Abstract: A study of the mass transfer performance for a pulsed disc and doughnut extraction column has been presented for a range of operating conditions. The mass transfer performance has been investigated for both directions of mass transfer. This study has examined the mass transfer coefficients which has incorporated the effects of back‐mixing in the continuous phase. The effect of operating variables including pulsation intensity and dispersed and continuous phase velocities on volumetric overall mass transfer coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In the current study, mass transfer performance of perforated rotating disc contactor for the water-acetone-toluene system is investigated.The effect of operating parameters including A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 26 dispersed and continuous phase velocities and agitation rate is considered for investigation of mass transfer in PRDC extraction column. The results revealed that the columnperformance increased with an increase in agitation rate, whereas it changesslightly with the continuous phase velocity.…”
Section: -Conclusionmentioning
confidence: 99%
“…In the current study, mass transfer performance of perforated rotating disc contactor for the water-acetone-toluene system is investigated.The effect of operating parameters including A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 26 dispersed and continuous phase velocities and agitation rate is considered for investigation of mass transfer in PRDC extraction column. The results revealed that the columnperformance increased with an increase in agitation rate, whereas it changesslightly with the continuous phase velocity.…”
Section: -Conclusionmentioning
confidence: 99%
“…[8] Furthermore, it is observed that the presence of mass transfer of acetone from dispersed phase to continuous phase leads to the formation of larger drops as dictated by correspondingly higher concentration of the solute in the draining film between two approaching drops than surrounding continuous liquid, irrespective of the operating regime. [40][41][42][43] The interfacial tension gradients will slow down the drainage and hinder coalescence. Consequently, the mass transfer from d !…”
Section: Influence Of Pulsation Intensity On the Mean Drop Sizementioning
confidence: 99%
“…Among the various types of extraction columns, the pulsed disc and doughnut extraction column is one type of extractor whose application has rarely been referred to the literature [13][14][15][16]. An installation of the pulsed disc and doughnut columns to treat the uranium solutions from Western Mining Corporations in South Australia has shown that these columns have a clear advantage over the mixer-settlers.…”
Section: Introductionmentioning
confidence: 97%